Escitalopram for Psychogenic Nausea and Vomiting: A Report of Two Cases - Wen-Yu Hsu; Si-Sheng Huang; Nan-Ying Chiu (Journal of the Formosan Medical Association, 2011)
Psychogenic nausea and vomiting is defined as vomiting without any obvious organic pathology or vomiting with a psychological etiology. The treatment for such a condition is a challenge in clinical practice. The first patient was a 46-year-old married factory worker who was repeatedly hospitalized for recurring bouts of nausea and vomiting. After consultation, she was diagnosed with major depressive disorder. The frequency of nausea and vomiting decreased after treatment with daily doses of 10–20 mg escitalopram. The second patient was a 37-year-old married teacher who had bouts of nausea and vomiting and was also hospitalized repeatedly. She was diagnosed with mixed anxiety–depressive disorder. After treatment with 10 mg/day escitalopram, her episodes of nausea and vomiting decreased. Escitalopram may be an effective treatment for psychogenic nausea and vomiting associated with depression.